A Low-complexity Video Coding Scheme Based on Compressive Sensing - Yantian Hou; Feng Liu (2011 Fourth International Symposium on Computational Intelligence and Design, 2011)
Traditional video coding method is able to achieve wonderful performance in data compressing. However, it has high complexity, which is not suitable for some environments where low complexity coding is needed. A new method of video coding which is based on compressive sensing is proposed. In this system, the sparsity of residual of successive frames is exploited, which is a crucial requirement in CS theory. This method encodes video frames in a fast and low-complexity way, while the compressive rate of data remains low. The reconstruction of original video frame, as well as the PSNR-rate curve under this framework, is given.